Auditory Neuropathy: Case Study with Hyperbilirubinemia - Simmons, Jeffrey L.; Beauchaine, Kathryn Laudin (Journal of the American Academy of Audiology, 2000)
Auditory neuropathy (AN) has been described in the literature as presenting with a combination of audiometric findings that include elevated behavioral audiometric thresholds, auditory brainstem response findings that are not consistent with audiometric findings, poor speech recognition, and present otoacoustic emissions (OAEs) and/or cochlear microphonics. Since the availability of clinical OAE testing, AN has come to be identified with increasing frequency; however, incidence and prevalence figures are unavailable. There is a great deal of discussion about the accurate diagnosis of AN, its characteristics, and its treatment. Some of this discussion is occurring on the Internet and over the telephones. The need to continue to provide information in accessible peer-reviewed journals is paramount. Following a review of the literature, a case study is presented of a boy who was diagnosed with AN as a newborn. He experienced hyperbilirubinemia and other neonatal health complications. His educational intervention was managed elsewhere until recently. Information is presented about the progression of the case over a 5–year period that includes audiologic data and communication development results.Abbreviations: AN = auditory neuropathy, CI = cochlear implant, CM = cochlear microphonic, DPOAE = distortion product otoacoustic emissions, DSL = Desired Sensation Level, IHC = inner hair cell, MRI = magnetic resonance imaging, OAE = otoacoustic emission, OHC = outer hair cell, SS = standard scores, TC = total communication
Keywords: Auditory brainstem response; auditory neuropathy; hearing disorder; hyperbilirubinemia; otoacoustic emission